2017
DOI: 10.1186/s40529-017-0202-x
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of Lilium callosum Sieb. et Zucc. in Taiwan after a fire allows propagation and renews the possibility of conservation

Abstract: Background Lilium callosum is native to Taiwan, but little is known about it since it has been considered extinct since 1915. After the rediscovery of this rare species after a fire in 2011 in Tunghsiao Township, intensive work has been conducted to count the number in the wild population, to develop a conservation strategy, and to understand its reproductive characteristics and even economic potential.ResultsTo conserve the germplasm of this population, three scales from a wild L. callosum plant were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…L. callosum is a widespread species in Asia, distributed from Taiwan to northern Russia. However, phylogenetic analysis using ITS sequences demonstrated that L. callosum from Taiwan is not clustered with other L. callosum accessions [456]. A limiting effect on the fitness of L. callosum in Taiwan was found to be the inability to produce meagre numbers of seeds in the native habitat.…”
Section: Analysis Of Embryogenesis With Embryo Rescue Technical Holdermentioning
confidence: 95%
See 2 more Smart Citations
“…L. callosum is a widespread species in Asia, distributed from Taiwan to northern Russia. However, phylogenetic analysis using ITS sequences demonstrated that L. callosum from Taiwan is not clustered with other L. callosum accessions [456]. A limiting effect on the fitness of L. callosum in Taiwan was found to be the inability to produce meagre numbers of seeds in the native habitat.…”
Section: Analysis Of Embryogenesis With Embryo Rescue Technical Holdermentioning
confidence: 95%
“…Once rediscovered, the species was micropropagated by culturing scales of the bulb on a modified basal MS medium [72] supplemented with 0.1 mg L −1 NAA, 0.1 mg L −1 BA, 1 g L −1 casein hydrolysate, and 3% sucrose. The explants were maintained at 25 ± 1 • C with a 12 h photoperiod and a light intensity of 5.6 µmol m −2 s −1 [456]. In addition, flowers from two regenerated plants were crossed by hand pollination, and immature ovules were cultured in vitro.…”
Section: Analysis Of Embryogenesis With Embryo Rescue Technical Holdermentioning
confidence: 99%
See 1 more Smart Citation